Descriptors for the Evaluation of Electrocatalytic Reactions: d‐Band Theory and Beyond. (13th October 2021) - Jiao, Shilong; Fu, Xianwei; Huang, Hongwen
Abstract: Closing the carbon‐, hydrogen‐, and nitrogen cycle with renewable electricity holds promises for the mitigation of the facing environment and energy crisis, along with the continuing prosperity of the human society. Descriptors bridge the gap between the physicochemical factors of electrocatalysts and their boosted activity and serve as guiding principles during the rational design of electrocatalysts. The optimal adsorption strength of key intermediates is potentially accessed under the tendentious guidelines proposed by indicators, such as d‐band center, Δ G H, E O*, coordination number (CN), bond length, etc. Here, in this review, a comprehensive summary of the recent advances achieved regarding the descriptors during the rational design of electrocatalysts that aims for the recycling of C/H/N‐containing chemicals is offered. The review is initiated by providing the necessity of the development of efficient electrocatalysts and then the physics behind the d‐band center is introduced. Then a summary of the recent progress relating to the development of electrocatalysts under the guidance of descriptors is reviewed. Following that, an extended discussion regarding the experimental or theoretical characterization of the d‐band center and the descriptors beyond it is provided. Finally, perspectives and challenges in this area are offered. Abstract : The descriptors bridge the gap between the structural design of the electrocatalysts and their boosted electrocatalytic performance to close the hydrogen, carbon, and nitrogen cycle, thus offering guiding principles for rational construction of electrocatalysts with desired activity, selectivity, and long‐term stability.